IoT enabled ventilator monitoring system for covid-19 patients - Mashoedah, .; Rochayati, U.; Hidayatulloh, Indra; Sony, A.; Ernawan, Ferda; Fardiansyah, .; Nuryanto, Apri
The use of the IoT protocol on medical equipment is expected to provide protection for medical personnel in dealing with Covid-19 patients, especially when medical personnel are monitoring and setting up an equipment. This study aims to (1) produce a monitoring and control system for a breathing apparatus (Ventilator) based on the Internet of Thing (IoT), (2) test the ventilator control function, (3) test the data transmission function with the IoT protocol. The method used is Define, Design, Develop, and Disseminate (4D). Data collection is done through (1) Testing and Observation (2) Limited field test. This research produces a control and monitoring system for mechanical ventilators. The mechanical ventilator consists of a gripper motion mechanism driven by a dc motor. The movement of the gripper creates pressure and releases pressure on the ambu bag. The depth of pressure exerted by the gripper is measured as the volume and pressure of the air delivered to the lungs. The rate of pressure exerted is measured as the velocity of air flowing into the lungs.